Development of the region in the context of innovations – opportunities and threats - Korenik, Stanisław (Rozwój regionu w kontekście innowacji – szanse i zagrożenia, 2016)
Regional development in the globalizing economy is a result of many factors. At the same time, this process may take different forms. Undoubtedly one of the factors that influence the development of the regions are innovations.Innovations are unquestionably a chance but at the same time a great challenge for regions. The article attempts to identify the importance of innovations in the development of the region
Biblioteka Regionalisty, 2016, Nr 16, s. 45-52
Keywords: disproportion; space; development of the region; endogenous resources; innovation; innovation system; dysproporcja; przestrzeń; rozwój regionu; zasoby endogeniczne; innowacyjność; system innowacji